Abnormal Heart Rhythms - Breijo-Marquez, Francisco R. (IntechOpen, 2015)
We know a lot of things about cardiac rhythms and their abnormalities, but there are some things that are still waiting to be discovered and, therefore, require more study. In this book, the authors put a little light on those matters, which are not well known yet. The authors have exposed some of such cardiac arrhythmias, especially those affecting the atria of the heart (with special emphasis on fibrillation and flutter atria). By means of this book, readers can broaden their knowledge about this specific topic of supraventricular arrhythmias. They can also find a special chapter on "Amiodarone" as a cardiac antiarrhythmic drug, which is very revealing, even today.